2020
DOI: 10.1002/nse2.20023
|View full text |Cite
|
Sign up to set email alerts
|

Promoting transdisciplinary learning through a summer course on climate, water, and agriculture

Abstract: Transdisciplinary approaches increasingly are needed to address complex environmental problems. Students can benefit from research and learning opportunities in which they investigate issues, integrate knowledge across disciplines, engage with stakeholders, collaborate with others, and devise solutions. This paper presents information on a 1-week intensive transdisciplinary course focused on climate, water, and agriculture for undergraduate and graduate students. The course, which was held at The Ohio State Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Extensive research into the learning impacts and implementation of these approaches showed the importance of students gaining real-world experience to develop competencies and sensitize them to social challenges (e.g. Brundiers et al, 2021;Lekies & Moore, 2020;Smith et al, 2013;Viegas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research into the learning impacts and implementation of these approaches showed the importance of students gaining real-world experience to develop competencies and sensitize them to social challenges (e.g. Brundiers et al, 2021;Lekies & Moore, 2020;Smith et al, 2013;Viegas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This belief is potentially modifiable as part of preservice teacher training and/or later professional development. Many previous researchers in this area have argued that preservice early childhood training needs to include more content regarding the complexities of nature and more direct experiences in nature [14,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…A transdisciplinary approach-or integrating multiple disciplines to teach an idea-is particularly useful in teaching climate change and sustainable development. To quote research offered by Lekies and Moore (2020), "Transdisciplinary methods draw from multiple and often unrelated disciplines, integrate and synthesize information, allow for new collaborations, foster mutual understanding, engage nonacademic stakeholders, and generate and apply new knowledge" (Lekies and Moore, 2020). Incorporating tools learned in social sciences, mathematics, and biology makes the content more relevant and relatable mimicking the same intricacies and connections made in real life.…”
Section: Best Practices and Rationale Of Our Curriculummentioning
confidence: 99%